PENDEKATAN KONSEP, METODE DAN PENGEMBANGANNYA PADA AUDIT LINGKUNGAN - Kristanto, Y . (Universitas Slamet Riyadi, 2006)
Abstract Auditor have to answer to obtained information in executing its audit duty, that is how to look into auditor to negative and also positive information in audit duty execution, do there difference among unversed and experienced auditor in answering to information both for negative and also positive. Besides require to pay attention factors like knowledge, experience, and also of auditor in obtaining and evaluating information and way of auditor approach in answering to this information relate to audit risk and responsibility. In its relation with duty complexity which is ordinary to be faced auditor also influenced experience and also knowledge its meaning auditor progressively often a auditor face complex duty more and more to increase knowledge and also its experience. So also at risk to audit faced by a auditor also will be influenced by experience from the auditor. Keywords: Environmental Audit, Concept, Method, Information, EMAS, stakeholders, financial auditors